An Economic History of Twentieth-Century Latin America
XIII, 329 p.
Keywords: This book explores the impact on Latin America of the extraordinary transformation of the international economy that took place in the half century or so that preceded the world depression of the 1930s. The authors show how the response varied in terms of both growth and distribution, shaped by varying preconditions, and by natural resources and geography. The interplay of economic developments with political and social structures had profound and varied effects on policy-making and on institutions that were of great significance for later decades.